Analisis Efektivitas Pajak Kendaraan Bermotor Dan Bea Balik Nama Terhadap Pendapatan Asli Daerah - Irsan, Muhammad; Sanjaya, Surya; Astari, Nining (Jurnal Riset AKuntansi dan Bisnis, 2024)
The sources of research data are primary data in the form of interviews and secondary data in the form of data on realization of PKB-BBNKB receipts obtained from UPT. North Medan Samsat. The decrease in revenue from the realization of motor vehicle taxes and transfer fees for motorized vehicles from 2018 to 2019 was due to taxpayers who still had not paid taxes owed and did not pay administrative witnesses that were imposed as well as decreased public purchasing power for new vehicles due to an increase in tariffs.  as well as the lack of public awareness in the payment of BBN-KB for used vehicles. Based on the calculation results of the analysis of the effectiveness and contribution of the transfer of title to motorized vehicles, it can be concluded that the effectiveness of motor vehicle tax revenues and the transfer of title of motor vehicles in 2017 and 2021 has been effective.